(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this article is to present a comparative analysis of the Business Administration Programs of Higher Education Institutions (HEI) in the city of Cartagena, Colombia, and Northwestern State University of Louisiana (NSU) in the United States within the framework of university social responsibility. This article is the product of a descriptive-comparative research, which studied a non-probabilistic convenience sample of 340 people, made up of the groups of interest: students (278), and teachers (62). The data collection techniques were conducted through surveys applied to the stakeholders identified for this research. The results show that the HEIs in Cartagena and the NSU are perceived by their stakeholders as having good practices framed in social responsibility policies. However, at NSU there is a greater awareness and appropriation of aspects that underpin the University Social Responsibility.